2018
DOI: 10.1021/acs.energyfuels.8b02467
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Nitrogen Isotope Compositions in Coals from the Huainan Coalfield, Anhui Province, China: Influence of the Distribution of Nitrogen Forms

Abstract: A combination of nitrogen isotope analysis and X-ray photoelectron spectroscopy techniques was used to characterize nitrogen isotopic compositions and organic nitrogen forms in a total of 11 coal samples from China. A range of δ 15 N values between −2.9‰ and +3.6‰ was observed in all coals, and the N-5 peak is predominant. The results show that a correlation exists between the δ 15 N value and the proportions of the N-5 peak and the sum of the N-6 and N-Q peaks. This suggests that the nitrogen isotopic composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…10 th century CE, reached a value of +16.3 ‰ in the 1870s CE, and then decreased to the lowest value of +9.8 ‰ by 2008 CE. Declining δ 15 N in post-industrial deposits may reflect NOx emissions from coal combustion, as coal δ 15 N values are approximately 0 ‰ (Ding et al 2018;Peterson and Fry 1987). δ 15 N can also decrease with increasing anthropogenic emissions from fossil fuel combustion and synthetic fertilizers (Freyer 1978).…”
Section: Stable Isotopes and Dietary Trendsmentioning
confidence: 99%
“…10 th century CE, reached a value of +16.3 ‰ in the 1870s CE, and then decreased to the lowest value of +9.8 ‰ by 2008 CE. Declining δ 15 N in post-industrial deposits may reflect NOx emissions from coal combustion, as coal δ 15 N values are approximately 0 ‰ (Ding et al 2018;Peterson and Fry 1987). δ 15 N can also decrease with increasing anthropogenic emissions from fossil fuel combustion and synthetic fertilizers (Freyer 1978).…”
Section: Stable Isotopes and Dietary Trendsmentioning
confidence: 99%
“…This means that the use of sedimentary δ 15 N profiles to interpret paleoenvironmental conditions in lakes is not as well constrained as in marine environments, and evaluation of thermally mature lacustrine formations even less so. As mentioned above, the δ 15 N values and C/N ratios for Type III kerogen and coals do reflect the influence of terrestrial organic material and are distinct from the Type I and Type II kerogen values (Rigby and Batts, 1986;Boudou et al, 2008;Ding et al, 2018;Xie et al, 2021). Analysis of two different lacustrine source rocks from the Junggar Basin of China found that crude oils from brackish lacustrine basins were more enriched in pyrrolic-N containing compounds derived from biological sources than crude oils from alkaline lacustrine settings (Zhang et al, 2020).…”
Section: Lacustrine Basinsmentioning
confidence: 91%
“…Similarly, the δ 15 N values x for coals and lacustrine and brackish-water oil shales are generally higher than for oil shales deposited under marine conditions, reflecting both organic matter source and the nitrogen utilization of the precursor organisms (Rigby and Batts, 1986). The δ 15 N values of coals, in particular, reflect the organic matter source and composition rather than maturity or diagenesis (Figure 2; Rigby and Batts, 1986;Ding et al, 2018;Xie et al, 2021). These distinctions between the marine and terrestrial organic matter sources indicates that if the nitrogen source or kerogen type is unknown, caution must be used when interpreting δ 15 N records in petroleum systems, as higher δ 15 N values could be a consequence of suboxic conditions characterized by predominant water column denitrification or reflect the presence of significant amounts of terrestrial input.…”
Section: Kerogen Typementioning
confidence: 99%
“…The isotopic composition of nitrogen in a sample is conventionally expressed as δ 15 N (δ 15 N (‰) = {( 15 N/ 14 N) sample /( 15 N/ 14 N) air – 1} × 1000). An increasing amount of N isotope data from coal is being reported, , and the continuous-flow isotope ratio mass spectrometer has become a popular method used to analyze N isotopes, , mainly due to its high efficiency, rather than the use of conventional labor-intensive methods, such as the Dumas combustion method ,, and Kjeldahl method . However, although more data are being reported, few studies are being conducted to evaluate analytical methods employed.…”
Section: Introductionmentioning
confidence: 99%